Synthesis of pseudo-indoxyl derivatives via sequential Cu-catalyzed SNAr and Smalley cyclization - Goriya, Yogesh; Ramana, Chepuri V. (Chemical Communications, 2013)
ortho-Bromophenyl sec-alkyl/sec-alkenyl ketones, on reaction with sodium azide in the presence of copper salts, undergo sequential SNAr followed by Smalley cyclization to provide pseudo-indoxyl derivatives. Some of these pseudo-indoxyl derivatives exhibit interesting fluorescent properties and broad Stokes shifts.